Scandinavia's monetary convergence with the European Community - Bernhard Duijm; Bettina Nürk (Intereconomics, 1992)
In the twelve months preceding the conclusion by the EFTA countries and the EC of the agreement on the establishment of a common European Economic Area in October 1991, the three Skandinavian EFTA members-Norway, Finland and Sweden-decided to tie their currencies to the ECU. What objectives do these countries hope to achieve by this move? What effects is it likely to have?
Keywords: 330